APPLICATION OF NANOSENSOR BASED SCREEN PRINTED ELECTRODE FOR ANALYSIS OF ARTIFICIAL SWEETENER FOR PHARMACISTS AND ANALYST IN PONTIANAK - Jiwanti, Prastika Krisma; Saputra, Mirza Ardella; Susilo, Raden Joko Kuncoroningrat; Hayaza, Suhailah; Amrillah, Tahta; Firmansyah, Mochamad Lutfi; Amalina, Ilma; Mulya, Fadjar; Rizki, Intan Nurul; Sari, Retno (Universitas Airlangga, 2024)
The development of nanotechnology in the world is very rapid, and the applications of nanotechnology can be felt in various fields in everyday life. For instance, to control food, nanotechnology plays a role in creating early detection tools for food additives, which are known to be dangerous if consumed by humans in excess, such as the presence of colorants that are not permitted or food additives that exceed tolerance limits. Nanosensors based on screen print electrodes (SPE) are devices that can be used for detection with various notable properties such as fast, sensitive and portable. Seeing the importance of developing and down streaming nanotechnology to society, education regarding the role of nanotechnology needs to be carried out. In this activity, nanotechnology applied in the manufacture of nanosensor devices was introduced, especially to analysts at the drug and food control center and the health service. Apart from that, through this activity, sustainable collaboration can be established between the community service team who are researchers in the field of nanosensors and users in the field who are drug and food regulatory bodies, to develop nanosensor technology according to needs in the field. This activity will be carried out in Pontianak, West Kalimantan, specifically aimed at pharmacists and analysts in the drug and food control center, health service, and industry and trade service (Disperindag). This activity will include education about nanotechnology applications in various fields as well as a demonstration on the use of SPE-based naosensor devices. From this event, in future the analyst may do the analysis in field without waiting long time analysis in laboratory. From this community service activities, scientific articles and publications can be produced in print/electronic media, as well as videos of community service activities, in accordance with the main performance indicators determined nationally.